CREATION OF A PROBIOTIC BIOLOGICAL PRODUCT BASED ON LACTOSE-UTILIZING MICROORGANISMS (Experimental biology, 2021)
Today 60% of the population of Kazakhstan suffers from hypolactasia. In addition, the production of lactose-free fermented milk products in the Kazakhstan market is observed in an insignificant amount. In this regard, the purpose of this scientific research is to develop a starter culture as a probiotic preparation based on lactic acid bacteria isolated from Kazakh traditional food products. The practical significance of the research lies in the ability to produce lactose-free fermented milk products in an industrial environment, based on the developed technology. Strains of Lactobacillus acidophilus, Enterococcus faecium were used as a starter culture. Our earlier studies have shown that lactobacilli have lactose-utilizing properties. Genetic identification of bacteria was carried out on the basis of the 16S rRNA gene; batch cultivation was used at different ranges of NaCl, pH. Experiments on the dynamics of growth were studied depending on the time of cultivation. Studies have shown that Lactobacillus acidophilus, Enterococcus faecium develop in an acidic pH˂7 environment. Selective breeding and development media are favorable, where the concentration of hydrochloric acid is about 5%. The applicability of the research results obtained is relevant for the microbiological, biotechnological and dairy industries. The practical significance of the results of this work lies in the import substitution of expensive probiotic preparations. The developed probiotic is cheaper than foreign counterparts at the price offer, since it is created on the basis of microorganisms isolated in the territory of the Republic of Kazakhstan.